Pola Baru Pengelolaan Media Digital Dalam Instagram @humasjogja - Sukmono, Filosa Gita; Surya Kencana, Adinda Putri (Unisba Press, 2022)
The use of digital media has been very influential in all circles. This phenomenon forces the government to adapt and familiarize itself with digital media. The problem of information in the midst of the pandemic shows the importance of both central and regional government’s official social media as a source of information or as media that can show that the government “cares” during the pandemic. This study aims to determine the communication strategy carried out by the Yogyakarta Government in managing Instagram @humasjogja. This is because the people of Yogyakarta always spread the posts uploaded by Yogyakarta’s Public Relations. This study uses a qualitative method. Based on the results of the study, the authors see that the Yogyakarta Government uses the official Instagram to appeal to the people of Yogyakarta, especially during the pandemic, by releasing new content and strategy. One of the content is “Sapa Aruh” which is a direct appeal from the Governor of Yogyakarta.